2019
DOI: 10.1038/s41541-019-0118-4
|View full text |Cite|
|
Sign up to set email alerts
|

Qß Virus-like particle-based vaccine induces robust immunity and protects against tauopathy

Abstract: Tauopathies, including frontotemporal dementia (FTD) and Alzheimer’s disease (AD) are progressive neurodegenerative diseases clinically characterized by cognitive decline and could be caused by the aggregation of hyperphosphorylated pathological tau (pTau) as neurofibrillary tangles (NFTs) inside neurons. There is currently no FDA-approved treatment that cures, slows or prevents tauopathies. Current immunotherapy strategies targeting pTau have generated encouraging data but may pose concerns about scalability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 66 publications
0
54
0
Order By: Relevance
“…Subsequent studies demonstrated that vaccines consisting of self-antigens arrayed on the surface of the VLPs could effectively induce anti-self antibody responses [52,53], that this ability is critically dependent on the density of the self-antigens displayed on VLPs [54,55], and that these interactions may be mediated by binding to surface-expressed IgD on naïve B cells [56]. These findings have led to the development of vaccine candidates that induce antibodies against self-antigens involved in chronic diseases, including angiotensin II (hypertension) [57], PCSK9 (cardiovascular disease) [58], amyloid-beta and hyper-phosphorylated tau (Alzheimer's Disease) [59,60], and others [61]. Several of these vaccines have been tested in human clinical trials [62].…”
Section: The Special Case Of Using Multivalent Vaccines To Break B-cementioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies demonstrated that vaccines consisting of self-antigens arrayed on the surface of the VLPs could effectively induce anti-self antibody responses [52,53], that this ability is critically dependent on the density of the self-antigens displayed on VLPs [54,55], and that these interactions may be mediated by binding to surface-expressed IgD on naïve B cells [56]. These findings have led to the development of vaccine candidates that induce antibodies against self-antigens involved in chronic diseases, including angiotensin II (hypertension) [57], PCSK9 (cardiovascular disease) [58], amyloid-beta and hyper-phosphorylated tau (Alzheimer's Disease) [59,60], and others [61]. Several of these vaccines have been tested in human clinical trials [62].…”
Section: The Special Case Of Using Multivalent Vaccines To Break B-cementioning
confidence: 99%
“…tau (Alzheimer's Disease) [59,60], and others [61]. Several of these vaccines have been tested in human clinical trials [62].…”
Section: The Special Case Of Using Multivalent Vaccines To Break B-cementioning
confidence: 99%
“…Another factor to consider is the cellular location of the antigen, in our case the tau protein. The tau protein is an intracellular protein and the anti-tau antibodies enter in the brain [28,29] and can be internalized in neurons [30]. However, the most likely hypothesis is that its mechanism of action consists in eliminating extracellular tau and, therefore, blocking transcellular spreading [51].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, future experiments will be performed to evaluate the expression by MVA of other tau isoforms or optimized tau fragments with a diminished microtubule stabilization, such as the C-terminal region of tau that has also been described as the most immunogenic region [55,58], or other regions as the N-terminal domain. Moreover, some tau fragments have been used with success in active immunization against AD [4,55], as well as a phosphorylated tau peptide bound to VLPs [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation